METEOROLOGICAL DROUGHT DEVELOPMENTS IN THAI BINH PROVINCE IN THE CONTEXT OF CLIMATE CHANGE - Thi Thu Hien, Nguyen; Thi Hang, Vu (HNUE Journal of Science: Journal of Natural Sciences, 2024)
This article presents the frequency and trends of meteorological drought in Thai Binh province for the period 1991-2021 and forecasts drought trends for the period 2025-2065 based on climate change scenarios. The PED drought index is calculated using the corresponding daily temperature and rainfall data for each of these periods. The results indicate that meteorological drought in Thai Binh can occur in both the dry and rainy seasons. During the period from 1991 to 2021, medium drought occurred in the dry season nearly once every ten years. Drought occurrences in both the rainy and dry seasons show an increasing trend in intensity and the number of drought months. In the future, during the period from 2025 to 2065, dry season drought will fluctuate less under the RCP4.5 scenario but will sharply increase in frequency and intensity under the RCP8.5 scenario. In the rainy season, drought is projected to increase in both scenarios. The number of drought months is relatively high and will rise significantly in both RCP4.5 and RCP8.5 scenarios. A notable aspect of this study is the analysis of meteorological drought trends for the period 2025-2065, based on climate change scenarios.